Exploring students misconceptions of science concepts in secondary school biology in Gusau, Zamfara State - Oluwatomisin Marvellous Ogundeji; Abdullahi Rabiu Bungudu; Aminu Ibrahim (Education and Development Research, 2025)
The main purpose of this study is to explore students’ misconception of science concepts in secondary school Biology in Gusau, Zamfara State. Three research questions and one null hypothesis guided the study. The study adopted descriptive survey research design. 1750 senior secondary school three (SS3) biology students of 2020/2021session in all the 25 public secondary schools in Gusau, Zamfara State, formed the population for the study. The sample size of 220 senior secondary three (SS3) students was used for the study. Simple random sampling and proportionate stratified random sampling techniques were used in composing the sample. Questionnaire on the source of students’ misconception of science biology concepts (QSSMSCB) and Students’ Conception Test (SCT) having 20 objective items developed by the researchers to measure students’ conception in Biology. Frequency and percentage were used to answer all the research questions and Chi-square were used in testing the null hypothesis of the study. The study found that: the Heart, Photosynthesis, Fertilization, Peristalsis and Gamete were the common misconceptions among secondary school Biology students in Gusau; Biology textbooks, teachers and traditional/religious beliefs were sources of misconceptions of science concepts among secondary schools in Gusau; and finally, the influence of gender on secondary school students’ conception of Biology in Gusau is not statistically significant. Based on the findings, the following recommendations were made among other, that: biology teachers should learn how to probe into students’ conceptions in a bit to help them grasp correct/clear explanation (i.e. conceptual understanding) of to-be-learnt concepts for better Understanding.